The Influence of Participation, Transparency, Accountability, and Utilization of Information Technology in the Management of Village Funds - Supartini; Syahriar Abdullah; Susilaningtyas Budiana Kurniawati; Istinganah Eni Maryanti (Journal of Social Knowledge Education (JSKE), 2025)
Purpose of the study: This study aims to determine the influence of (1) participation, (2) transparency, (3) accountability and utilization of information technology in the management of village funds in Bandardawung village, Tawangmangu Karanganyar sub-district. Methodology: This study uses primary data sourced from respondents' answers. The population in this study was 104 community leaders of Bandardawung village. The sample in this study was calculated using the Solvin formula of 83 people. The data collected in this research was 52. The analysis method used was multiple linear regression and was processed using SPPS software version 26. Main Findings: From the partial test, the variable with the greatest influence on village fund management is the variable of information technology utilization, amounting to 12.83. Adjusted R square value indicates that collectively participation, transparency, accountability and utilization of information technology contribute 94,2%. The remaining 5.8% is another factor outside this study. Novelty/Originality of this study: Previous research only discussed the influence of participation, transparency and accountability on village fund management. The author has not found any research that tests participation, transparency, accountability and the use of information technology in village fund management. This study adds the variable of information technology utilization to maintain budgetary order and discipline in village fund management.